2020
DOI: 10.7759/cureus.7836
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency in Children with Type 1 Diabetes Mellitus

Abstract: Background In the recent years, controversy has emerged regarding the relationship between vitamin D deficiency and the potential effects it could have on glycemic control in patients with type 1 diabetes mellitus (T1D). This study investigates the prevalence of vitamin D insufficiency/deficiency in pediatric patients with T1D from a single, large volume practice. Methods This was a retrospective chart review that collected clinical/demographic data as well as serum 25(OH) D levels from medical records of 395 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
2
14
0
1
Order By: Relevance
“…We observed a higher prevalence of vitamin D deficiency (89%) in children with T1D than few other studies. [20,23] Majority (64%) of controls had low serum levels of 25(OH)D levels in this study, comparable to a study conducted in a healthy pediatric population from India. [21,24] In our study, there was no significant correlation between vitamin D levels and duration of sun exposure, calcium intake, time spent on screen, HbA1c levels, duration of disease, and physical activity score in cases.…”
Section: Intra-assay Coefficient Of Variation (%)supporting
confidence: 84%
See 1 more Smart Citation
“…We observed a higher prevalence of vitamin D deficiency (89%) in children with T1D than few other studies. [20,23] Majority (64%) of controls had low serum levels of 25(OH)D levels in this study, comparable to a study conducted in a healthy pediatric population from India. [21,24] In our study, there was no significant correlation between vitamin D levels and duration of sun exposure, calcium intake, time spent on screen, HbA1c levels, duration of disease, and physical activity score in cases.…”
Section: Intra-assay Coefficient Of Variation (%)supporting
confidence: 84%
“…The previous studies showed mixed results pertaining to these biochemical parameters. Few studies showed comparable results to our study [22,23,25,26] and few other studies had contradicting results. [19,22] Bone turnover markers predict the increased fracture risk and rapid bone loss, independent of BMD.…”
Section: Intra-assay Coefficient Of Variation (%)supporting
confidence: 76%
“…The geographic location of Poland with low sunlight and insufficient exposure to ultraviolet light is probably the main cause of such finding. However, VDD in individuals with T1D is very common, even in a sun-rich environment (23). Moreover, the prevalence of VDD is higher in young patients with T1D compared to adolescents without diabetes (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous prospective cohort studies have suggested that compared to other lipid pro les, LDL-C increased in childhood is the strongest predictor for the risk of dyslipidemia and cardiovascular disease in adulthood [8,9]. The de ciency or insu ciency of Vitamin D levels in T1DM children is highly prevalent [10]. Immunologic effects of Vitamin D on human health and disease have been demonstrated [11].…”
Section: Introductionmentioning
confidence: 99%
“…But the link between Vitamin D levels and LDL-C has not received much attention. Considering the high prevalence of vitamin D de ciency among T1DM children, its potential health implications, and its convenience of treatment, it is necessary to consider regularly screening T1DM children for vitamin D insu ciency or de ciency [10].…”
Section: Introductionmentioning
confidence: 99%